2021
DOI: 10.1002/ieam.4409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating sedimentary PAH bioavailability based on equilibrium partitioning and passive sampling at the Dover Gas Light Superfund Site (Dover, Delaware, USA)

Abstract: From 1859 to 1948, the Dover Gas Light plant produced combustible gas for industrial, commercial, and residential applications using pine resin, coking coal, oil, and wood, and finally, a coal-gas process. Waste coal tar was discharged into the St. Jones River in Dover, Delaware (USA), via a ditch and culvert and, following plant closure in the 1940s, through groundwater flow from structures buried on the site. By the end of the 20th century, polycyclic aromatic hydrocarbon (PAH) contamination of the sediments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
4
5
0
Order By: Relevance
“…Under nonequilibrium conditions, the f eq for the amount of each PRC lost from the PED was calculated by Equation (2): feqPRC=(CPRCiCPRCf)CPRCi <math xmlns="http://www.w3.org/1998/Math/MathML" altimg="urn:x-wiley:07307268:media:etc5896:etc5896-math-0002" display="block" wiley:location="equation/etc5896-math-0002.png" displaystyle="true"><mrow><mrow><msub><mi>f</mi><mrow><mtext>eq</mtext><mo>\unicode{x02212}</mo><mtext>PRC</mtext></mrow></msub><mo>\unicode{x0003D}</mo><mfrac><mrow><mo stretchy="false">(</mo><mrow><msub><mi>C</mi><mtext>PRCi</mtext></msub><mo>\unicode{x02212}</mo><msub><mi>C</mi><mtext>PRCf</mtext></msub></mrow><mo stretchy="false">)</mo></mrow><msub><mi>C</mi><mtext>PRCi</mtext></msub></mfrac></mrow></mrow></math>where f eq–PRC is the fractional equilibria for the PRC; C PRCi is the concentration of PRC in the PED at construction, and C PRCf is the concentration of PRC remaining in the PED after deployment (see the calculated f eq–PRC values in the Supporting Information, Tables S2 and S3). Our study was consistent with published guidance and other studies by using three representative PRCs covering a range of fugacities (Burgess et al, 2021; Choi et al, 2013; Fernandez et al, 2009; Ghosh et al, 2014; Reitsma et al, 2013; USEPA, 2017). Fernandez et al (2009) showed that the accuracy of using a few PRCs for assessing multiple target compounds was in good agreement with C free estimates when one was using target analyte–matched PRCs, thereby eliminating the need to have a full one‐to‐one PRC to target analyte match.…”
Section: Methodssupporting
confidence: 92%
See 4 more Smart Citations
“…Under nonequilibrium conditions, the f eq for the amount of each PRC lost from the PED was calculated by Equation (2): feqPRC=(CPRCiCPRCf)CPRCi <math xmlns="http://www.w3.org/1998/Math/MathML" altimg="urn:x-wiley:07307268:media:etc5896:etc5896-math-0002" display="block" wiley:location="equation/etc5896-math-0002.png" displaystyle="true"><mrow><mrow><msub><mi>f</mi><mrow><mtext>eq</mtext><mo>\unicode{x02212}</mo><mtext>PRC</mtext></mrow></msub><mo>\unicode{x0003D}</mo><mfrac><mrow><mo stretchy="false">(</mo><mrow><msub><mi>C</mi><mtext>PRCi</mtext></msub><mo>\unicode{x02212}</mo><msub><mi>C</mi><mtext>PRCf</mtext></msub></mrow><mo stretchy="false">)</mo></mrow><msub><mi>C</mi><mtext>PRCi</mtext></msub></mfrac></mrow></mrow></math>where f eq–PRC is the fractional equilibria for the PRC; C PRCi is the concentration of PRC in the PED at construction, and C PRCf is the concentration of PRC remaining in the PED after deployment (see the calculated f eq–PRC values in the Supporting Information, Tables S2 and S3). Our study was consistent with published guidance and other studies by using three representative PRCs covering a range of fugacities (Burgess et al, 2021; Choi et al, 2013; Fernandez et al, 2009; Ghosh et al, 2014; Reitsma et al, 2013; USEPA, 2017). Fernandez et al (2009) showed that the accuracy of using a few PRCs for assessing multiple target compounds was in good agreement with C free estimates when one was using target analyte–matched PRCs, thereby eliminating the need to have a full one‐to‐one PRC to target analyte match.…”
Section: Methodssupporting
confidence: 92%
“…where f eq-PRC is the fractional equilibria for the PRC; C PRCi is the concentration of PRC in the PED at construction, and C PRCf is the concentration of PRC remaining in the PED after deployment (see the calculated f eq-PRC values in the Supporting Information, Tables S2 and S3). Our study was consistent with published guidance and other studies by using three representative PRCs covering a range of fugacities (Burgess et al, 2021;Choi et al, 2013;Fernandez et al, 2009;Ghosh et al, 2014;Reitsma et al, 2013;USEPA, 2017). Fernandez et al (2009) showed that the accuracy of using a few PRCs for assessing multiple target compounds was in good agreement with C free estimates when one was using target analyte-matched PRCs, thereby eliminating the need to have a full one-to-one PRC to target analyte match.…”
Section: Calculation Of Porewater Passive Sampler Concentrationssupporting
confidence: 92%
See 3 more Smart Citations